Determinants and Outcome of Information Technology Governance (ITG) Effectiveness to Organizational Performance: An Empirical Study of Public Listed Companies (PLC) in Malaysia - Ching, Kai Hsien (2014)
Malaysia has realised the importance of Information Technology Governance (ITG) in organizations which is also strongly driven by the implementation of corporate governance. As information technology advances from time to time, the ability of organizations to combine information technology resources to respond to the complexity business environment in order to improve organizational performance have also increased. Effective ITG has become very crucial and vital for corporate companies in conducting their business.